Pemanfaatan Limbah Minyak Jelantah Dalam Pembuatan Lilin Aromaterapi Di Kelurahan Harjosari II Medan Amplas - Irpan Arpandi Batubara; Diah Arthasari; Dinda Taringan; Divan Sinurat; Effriana F Sihaloho; Eka Dian Lestari; Elisa Kusumawati Silalahi; Elvayana Silitonga (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
A community service project entitled "Utilization of Used Cooking Oil in Making Aromatherapy Candles" involving Family Welfare Movement (PKK) women in Harjosari II Village, Jl. Dwikora No. 3, Medan Amplas District, North Sumatra Province, was conducted on April 29, 2025. The objective of this activity was to reduce environmental pollution caused by used cooking oil waste by processing it into aromatherapy candles. The used cooking oil waste was then developed into aromatherapy candles. Thus, household waste in the form of used cooking oil, which can cause environmental pollution, can be processed into a useful product and can increase household income. The target outputs are an aromatherapy candle product and a Bina Desa community service journal. To achieve these outputs, the methods applied include outreach, training, and hands-on practice to enhance the skills and creativity of participants. It is hoped that from this training, participants will gain knowledge and insight into processing used cooking oil and can also develop creative and innovative business ideas.